Extracorporeal CO2 removal and regional citrate anticoagulation in an experimental model of hypercapnic acidosis. Issue 8 (26th February 2019) - Morimont, Philippe; Habran, Simon; Desaive, Thomas; Blaffart, Francine; Lagny, Marc; Amand, Theophile; Dauby, Pierre; Oury, Cecile; Lancellotti, Patrizio; Hego, Alexandre; Defraigne, Jean‐Olivier; Lambermont, Bernard
Abstract: Low flow extracorporeal veno‐venous CO2 removal (ECCO2 R) therapy is used to remove CO2 while reducing ventilation intensity. However, the use of this technique is limited because efficiency of CO2 removal and potential beneficial effects on pulmonary hemodynamics are not precisely established. Moreover, this technique requires anticoagulation that may induce severe complications in critically ill patients. Therefore, our study aimed at determining precise efficiency of CO2 extraction and its effects on right ventricular (RV) afterload, and comparing regional anticoagulation with citrate to systemic heparin anticoagulation during ECCO2 R. This study was performed in an experimental model of severe hypercapnic acidosis performed in two groups of three pigs. In the first group (heparin group), pigs were anticoagulated with a standard protocol of unfractionated heparin while citrate was used for ECCO2 R device anticoagulation in the second group (citrate group). After sedation, analgesia and endotracheal intubation, pigs were connected to a volume‐cycled ventilator. Severe hypercapnic acidosis was obtained by reducing tidal volume by 60%. ECCO2 R was started in both groups when arterial pH was lower than 7.2. Pump Assisted Lung Protection (PALP, Maquet, Rastatt, Germany) system was used to remove CO2 . CO2 extraction, arterial pH, PaCO2 as well as systemic and pulmonary hemodynamic were continuously followed. Mean arterial pH was normalized to 7.37 ± 1.4 at an extracorporeal blood flow of 400 mL/min, coming from 7.11 ± 1.3. RV end‐systolic pressure increased by over 30% during acute hypercapnic acidosis and was normalized in parallel with CO2 removal. CO2 extraction was not significantly increased in citrate group as compared to heparin group. Mean ionized calcium and MAP were significantly lower in the citrate group than in the heparin group during ECCO2 R (1.03 ± 0.20 vs. 1.33 ± 0.19 and 57 ± 14 vs. 68 ± 15 mm Hg, respectively). ECCO2 R was highly efficient to normalize pH and PaCO2 and to reduce RV afterload resulting from hypercapnic acidosis. Regional anticoagulation with citrate solution was as effective as standard heparin anticoagulation but did not improve CO2 removal and lead to more hypocalcemia and hypotension.